2006
DOI: 10.1021/ja057733+
|View full text |Cite
|
Sign up to set email alerts
|

Can the Disproportion of Oxidation State III Be Favored in RuII−OH2/RuIVO Systems?

Abstract: Three new Ru-aqua complexes containing a mixed carbene and pyridylic ligands with general formulas [Ru(CNC)(bpy)(H2O)](PF6)2 (1) (CNC is 2,6-bis(butylimidazol-2-ylidene)pyridine; bpy is 2,2'-bipyridine) and cis-/trans-[Ru(CNC)(nBu-CN)(H2O)](PF6)2 (cis-2 and trans-2) (nBu-CN is 2-(butylimidazol-2-ylidene)pyridine) have been prepared and structurally characterized both in the solid state (monocrystal X-ray diffraction analysis for 1 and for the related complex trans-[Ru(Br)(CNC)(nBu-CN)](PF6)) and in solution (f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 16 publications
3
87
0
1
Order By: Relevance
“…An interesting feature of the Pourbaix diagram for 2 IV (OH) + is the pH 10-14 zone, that has been built by extrapolating the values of the V/IV couple at this pH and by assuming that the redox potential for the Ru V =O/Ru IV =O couple for [Ru IV (bda)(Me-py)2(O) eq ], 3 IV (O) (1.12 V), 15 is the same as for 2 IV (O) (Me-py is 4-methylpyridine). This assumption is based on Lever's approach 22,23,24 where it is shown that the Ru III /Ru II couple for a set of complexes can be calculated based on additive contribution of their respective ligands bonded to the first coordination sphere. In the present case, complexes 2 IV (O) and 3 IV (O) can be considered as "pseudo isomers" since in both cases the first coordination sphere is occupied by 4 pyridyl groups, two carboxylato and one terminal oxo ligand (see drawn structures Chart 1).…”
Section: Redox Properties and Water Oxidation Catalysismentioning
confidence: 99%
“…An interesting feature of the Pourbaix diagram for 2 IV (OH) + is the pH 10-14 zone, that has been built by extrapolating the values of the V/IV couple at this pH and by assuming that the redox potential for the Ru V =O/Ru IV =O couple for [Ru IV (bda)(Me-py)2(O) eq ], 3 IV (O) (1.12 V), 15 is the same as for 2 IV (O) (Me-py is 4-methylpyridine). This assumption is based on Lever's approach 22,23,24 where it is shown that the Ru III /Ru II couple for a set of complexes can be calculated based on additive contribution of their respective ligands bonded to the first coordination sphere. In the present case, complexes 2 IV (O) and 3 IV (O) can be considered as "pseudo isomers" since in both cases the first coordination sphere is occupied by 4 pyridyl groups, two carboxylato and one terminal oxo ligand (see drawn structures Chart 1).…”
Section: Redox Properties and Water Oxidation Catalysismentioning
confidence: 99%
“…The σ-donor/π-acceptor properties of the tri-and bidentate ligands bound in mononuclear Ru WOCs represented by complexes 8-10 (Chart 4) play important roles in stabilizing higher metal oxidation states [38,39] and further facilitating water oxidation e.g., by lowering redox potentials, increasing the thermodynamic driving force or decreasing energy barriers [32]. Therefore, smart modification or variation of ligands in WOCs is one of the major challenges in order to further improve the catalytic activity towards water oxidation.…”
Section: Ruthenium Complexes With An Axial Aqua Ligandmentioning
confidence: 99%
“…They revealed an interesting linear correlation between the number of carbene ligands in the complexes and ΔE 1/2 where each carbene unit causes a 100 mV decrease in the ΔE 1/2 value. The parameter ΔE 1/2 is defined as the difference between E 1/2 (Ru IV/III ) and E 1/2 (Ru III/II ) involved in the two PCET processes and the exact values of these two pH-dependent redox potentials can be extracted from Pourbaix diagrams [39]. [29].…”
Section: Chartmentioning
confidence: 99%
“…The conformation of the saturated ring thus does not seem to have any noticeable influence on the structure, as found in other coordination complexes incorporating (CH 2 ) 3 -bridged donor atoms. [46,47] [39,[41][42][43][44][45] and are at the short end of the distances observed in Ru carbene complexes, in general (1.91-2.20 Å, av. 2.06(5) Å].…”
Section: Resultsmentioning
confidence: 99%